Peran Guru dan Gerakan Literasi Sekolah dalam Meningkatkan Literasi Sejarah Siswa Kelas XI di SMA Negeri 3 Pematangsiantar - Asnewastri Asnewastri; Andres M. Ginting; Ahmad Fakhri Hutauruk; Resmi Resmi; Ahmad Arif Budiman Nasution (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2023)
Teachers play a crucial role as stakeholders in ensuring the continuity of literacy movements in schools. They undertake various efforts to sustain and develop school-based literacy programs, particularly in history. To this end, teachers can take several steps to promote and maintain the school's history literacy movement, such as planning and implementing the school's literacy history movement process. The research aims to determine the literacy skills of class XI students in lesson planning at SMAN 3 Pematangsiantar and to comprehend the role of teachers in fostering student literacy history in the learning process. A descriptive qualitative method was used to analyze descriptive data by describing the research results. The study utilized observation, interviews, and documentation to collect data from the principal, homeroom teacher, and class XI students. The study's findings suggest that teachers at SMAN 3 Pematangsiantar foster literacy movements through planning and processes implemented in the stages of habituation, development, and learning. Teachers can encourage students to participate in literacy programs by incorporating reading programs into the curriculum, such as a one-hour reading program or a reading lesson before class, and using various media, such as bulletin boards, to promote literacy movements. In addition, teachers and parents play essential roles in managing and supervising students since students learn not only at school but also actively learn at home.